Precision Dosing of Meropenem in Adults with Normal Renal Function: Insights from a Population Pharmacokinetic and Monte Carlo Simulation Study - Kim, Yong Kyun; Kang, Gaeun; Zang, Dae Young; Lee, Dong Hwan (Antibiotics (Basel), 2024)
This study aimed to develop a population pharmacokinetic (PK) model for meropenem in healthy adults and explore optimal dosing regimens for patients with normal renal function. PK samples were obtained from 12 healthy participants, which were analyzed using noncompartmental analysis and nonlinear mixed-effect modeling. The PK profiles of meropenem were characterized using a two-compartment model, and serum creatinine level was identified as a significant covariate affecting total clearance. Monte Carlo simulations were conducted using this model to inform dosing recommendations. The target index for meropenem efficacy was defined as the cumulative percentage over 24 h during which free (f) drug concentration exceeded the minimum inhibitory concentration (MIC) under steady state conditions (fT>MIC). These simulations indicated that the current dosage regimen of 1 g for 30 min infusions every 8 h achieved a 90% probability of target attainment (PTA) for 40%fT>MIC when the MIC was <2 mg/L. However, to achieve more stringent therapeutic targets, such as a 90%PTA for 100%fT>MIC or a 90%PTA for 100%fT>4MIC, higher doses administered as 3 h extended infusions or as continuous infusions may be necessary. These results highlight the need for model-informed precision dosing to enhance the efficacy of meropenem therapy across various MIC levels and therapeutic targets.